Гекзаметр у поезії Лесі Українки (власне гекзаметричні форми) - Бунчук, Борис; Bunchuk, Borys (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті показано, що власне гекзаметричні твори Лесі Українки – це форми з ознаками грецького виду гекзаметра, здебільшого перекладні силабо-тонічні структури з ритмом шестистопового цезурованого дактиля, із невеликою кількістю п’ятистопових, мінімальною кількістю дольникових версів, із незначною перевагою жіночої цезури й домінуванням жіночих закінчень. Іноді з’являються внутрішні рими, частка рядків із перенесеннями – здебільшого в межах 14–17 %. The article deals with the following works of Lesia Ukrainka with the charectiristics of properly hexameter forms: translated «The Hymn of the Indra’s Victory over Ahi», «The Hymn to the Sun», the second poem of the distich «The Hymn to the Dawn», original work «A Secret Gift». It was shown, that proper hexameter works of the poetess are the forms with the features of the hexameter of the Greek type, mostly translated (80 %) syllabic-tonic structures with the rhythm of six-foot caesural dactyl (from 76 to 94 %), with a little number of five-foot (from 6,5 % in «The Hymn of the Indra’s Victory over Ahi» to 21 % in the second poem of the distich «The Hymn to the Dawn»), a minimum number of accentual verse – from 0 to 9,5 % of lines, with a slight predominance (3:2) of female caesura and female endings. There is a little occurrence of internal rhymes (from 0 to 6,25 %), the part of lines with the transference – from 2,5 to 31,25 %, mostly within 14–17 %.
Hexameter in the Poetry of Lesia Ukrainka (Proper Hexameter Forms)
Keywords: гекзаметр; силабо-тоніка; шестистоповий дактиль; цезура; закінчення рядків; hexameter; syllabic-tonics; six-foot dactyl; caesura; the ending of the lines